Effect of Different Filters on Growth and Survival of Cachama (Colossoma macropomum) in the Recirculation System - Nuhaya Rafi Fauzan; Iskandar Putra; Mulyadi Mulyadi (Faculty of Fisheries and Marine, Universitas Riau, 2024)
The recirculation system, in principle, is the reuse of water that has been removed from cultivation activities. Cachama (Colossoma macropomum) is a relatively high economic value fishery commodity. This study aimed to obtain the best filter dose for water quality on the survival of cachama. The experimental method used a completely randomized design with six permitted treatments and three replications. The treatment used was P0 (without filter) with P1 (100% charcoal filter), P2 (100% zeolite filter), P3 (50% charcoal and 50% zeolite filter), P4 (25% charcoal and 75% zeolite filter), and P5 (75% charcoal and 25% zeolite filter) the fish kept for 50 days. The results of this study showed that the best treatment was P4 (25% charcoal and 75% zeolite filter), which resulted in a recent weight growth of 6.12 g, static length growth of 4.86 cm, growth rate specific growth of 2.08%, survival of 100%, and food conversion ratio of 1.95. Providing 25% charcoal and 75% zeolite filters affects water quality, growth, and survival rate.